1983
DOI: 10.1021/jo00153a029
|View full text |Cite
|
Sign up to set email alerts
|

Activation parameters and location of the transition state in the retro-Diels-Alder reaction of a 7-oxabicylo[2.2.1]hept-5-ene derivative

Abstract: l-Chloro-2-(JV-chIoro-p-toluenesulfonamido)acenaphthene. To a well-stirred cold (0-2 °C) solution of 2.01 g of acenaphthylene in 15 mL of CH2C12 was added dropwise (10 min) a solution of 3.2 g of Cl2NTs in 15 mL of CH2C12. Workup as described above followed except that CC14 at -30 °C was used in place of ether at 0-2 °C to triturate the crude solid. The insoluble portion (0.9 g, mp 149-152 °C) was identified as 1chloro-2-p-toluenesulfonamidoacenaphthene (see below). The CC14 filtrate was evaporated and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…A plot of ln k versus 1/ T according to the Arrhenius equation (Figure 3) yielded 21 kJ · mol −1 as the activation energy ( E a ). Values ranging from 41 to 161 kJ · mol −1 for E a have been reported for retro D‐A processes in which pairs of diene/dienophile molecules different from those in our system are involved 6,8,9,12,19,20. However, no values of E a have been found for the retro D‐A reaction taking place within a crosslinked polymer system.…”
Section: Resultscontrasting
confidence: 58%
“…A plot of ln k versus 1/ T according to the Arrhenius equation (Figure 3) yielded 21 kJ · mol −1 as the activation energy ( E a ). Values ranging from 41 to 161 kJ · mol −1 for E a have been reported for retro D‐A processes in which pairs of diene/dienophile molecules different from those in our system are involved 6,8,9,12,19,20. However, no values of E a have been found for the retro D‐A reaction taking place within a crosslinked polymer system.…”
Section: Resultscontrasting
confidence: 58%
“…This surprising result could be confirmed by three independent studies. In the two earlier studies G. Jenner et al and N. S. Isaacs et al found the ratio ∆V ≠ /∆V in the Diels-Alder reaction of furan with acrylonitrile [23] and that of N-benzoylpyrrole with N-phenylmaleic imide [24] to be larger than unity (Φ = 1.06 and 1.37, respectively). The cycloadducts isolated from both reactions Table 1 Molar volumes, V, van der Waals Volumes, V W , and packing coefficients, η, calculated for acyclic and cyclic ground and transition structures needed for the explanation of the pressure effect on the Diels-Alder reaction of 1,3-butadiene with ethene.…”
Section: Diels-alder Reactions Mechanistic Aspectsmentioning
confidence: 94%
“…Very large variations of the ratio V = / V r-n (from 1.0 to 1.69) were observed in the reaction of 1 with trans-1-methoxybutadiene in different solvents [29]. There is a direct experimental validation of the acceleration of some retro-Diels-Alder reactions under elevated pressure [2][3][4][5].…”
Section: Kinetic Measurements At High Pressurementioning
confidence: 99%